Small scale mechanized paddy rice in-bin dryer - Errasquin, Harry Alan P. (PSU Urdaneta Campus Research Journal, 2015)
The researchers of this study built a small scale mechanized paddy rice in-bin dryer considering the farmers with small holdings, this kind of dryer is space efficient and easy to operate. The design is simple and portable and it uses the principle of low-temperature air convection system. The mechanized dryer consists for main components; motor, fan, coil resistor and partition. To prove that the dryer is an effective small scale mechanized dryer that holds a capacity of 500kg of paddy rice, tests were conducted at Barangay Cabilaoan, Laoac, Pangasinan. The researchers of this project measured required parameters using specific tools to evaluate all the data gathered and determine the effectiveness and social acceptability of mechanized paddy rice in-bin dryer. Based on the findings, the researchers concluded that the project design would also bring a good drying performance for paddy rice. The researchers also considered the ambient temperature that would give immense factor in the drying performance of the project design. The researchers concluded that in-bin dryer is also good to become an alternative way for drying the paddy rice especially during rainy seasons and rapid change of weather condition which could be used by farmers in remote areas that depends on sun drying and because of large scale mechanized dryer available in the market, this type of dryer is suitable for them that it only needs a minimal amount of paddy to be put in dryer which also a good solution to dry the paddy during unfavorable weather condition.